Phase diagrams of the AgIn5Se8–AgGaSe2 and AgIn5Se8–Ga2Se3 systems of the quasi-ternary system Ag2Se–Ga2Se3–In2Se3 - Ivashchenko, Inna A.; Danyliuk, Iryna; Olekseiuk, Ivan D.; Іващенко, Інна Алімівна; Данилюк, Ірина; Олексеюк, Іван Дмитрович (Львівський національний університет ім. Івана Франка, 2012)
Using X-ray diffraction, differential-thermal and microstructural analyses and microhardness measurements, the quasi-binary systems AgIn5Se8–AgGaSe2 and AgIn5Se8–Ga2Se3 were investigated. Based on the results of the research, their phase diagrams were constructed
Keywords: X-ray phase analysis; Differential-thermal analysis; Microstructural analysis; Microhardness; Phase diagram